1973
DOI: 10.1139/v73-466
|View full text |Cite
|
Sign up to set email alerts
|

The Pulse Radiolysis of Penicillamine and Penicillamine Disulfide in Aqueous Solution

Abstract: Aqueous solutions of penicillamine (RSH) and penicillamine disulfide (RSSR) have been pulse irradiated at several pH's and the ensuing reactions studied. The rate constant for the reaction of solvated electrons with penicillamine disulfide decreases from 7.3 × 10−9 M−1 s−1 at pH 7 to 0.8 × 109 M−1 s−1 at pH 10. The first-order rate constant for the decomposition of the resulting radical anion, RSSR−, increases from 1.77 × 106 s−1 at pH 7 to 6.5 × 106 s−1 at pH 10. Both of these pH effects are attributed to dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 14 publications
5
51
0
Order By: Relevance
“…6 was published has shown that the value of 16 used for pH 10 was too low. 4 The correct value is 60 t 3, which is in better agreement with an earlier result of Purdie and co-workers (18). Since Kl determines the magnitude of 0 and the fractions of the two forms of radicals, this finding necessitated a re-evaluation of k I 7 and k18.…”
Section: Analysis Of the Photostationary Statessupporting
confidence: 86%
See 1 more Smart Citation
“…6 was published has shown that the value of 16 used for pH 10 was too low. 4 The correct value is 60 t 3, which is in better agreement with an earlier result of Purdie and co-workers (18). Since Kl determines the magnitude of 0 and the fractions of the two forms of radicals, this finding necessitated a re-evaluation of k I 7 and k18.…”
Section: Analysis Of the Photostationary Statessupporting
confidence: 86%
“…Thus, writing the formulae for the rates of reduction and oxidation on the left and right respectively, one has Here k17, k18, and k19 refer to the oxidation reactions [17], [18], and [19], the rate constants of which were reported in ref. 1201…”
Section: Analysis Of the Photostationary Statesmentioning
confidence: 99%
“…+ CysH + OHabove p H 7 and an analogous reaction has been postulated in penicillamine (6). However, further work will be required to confirm the occurrence of reaction 27 for the protonated form of the anion.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies of the y (1, 2) and pulse radiolysis (3,4) of aqueous oxygen free solutions of cysteine (HSCH,CH(NH,+)CO,-) and the related molecule cysteamine (HSCH,CH,NH,+) (5) have shown that the major products can be explained by the following mechanism, in which the abbreviation CysSH is used for the cysteine structure : More recently Purdie et al (6) have investigated the radiolysis of penicillamine (HSC-(CH3),CH(NH,+)CO2-= HSPen) and have found clear evidence for the production of a significant yield of penicillamine trisulfide (PenSSSPen). Since this behavior is quite different from previous observations of cysteine radiolysis and may have implications for an understanding of differences in their abilities as protectors (6), we have reinvestigated the cysteine system to determine whether any trisulfide is in fact formed.…”
Section: Introductionmentioning
confidence: 99%
“…The extensively studied physical-chemical properties of D-and L-penicillamine and their metal complexes are detailed in the following references, which provide excellent access to the literature: Budzinski & Box 1971, Cockerill et al 1974, Cothern et al 1976, Copeland 1970, Doornbos & Feitsma 1967, Freeman et al 1976, Friedman 1973, Lal et al 1975, Letter & Jordan 1975, Purdie et al 1973, Rao et al 1973, Rabenstein & Fairhurst 1975, Rosenfield & Parthasarathy 1975, Snow et al 1975, Thich et al 1974, Vasiliev et al 1973, Vasiliev et al 1974, Wu & Kuntz 1975 Metal Binding Penicillamine is used therapeutically to increase excretion of copper by patients who suffer from Wilson's disease (hepatolenticular degeneration) (Friedman 1973). This disease is caused by inherited error in copper metabolism and is characterized by an accumulation of copper in the body.…”
Section: Syntheses Andphysicochemical Propertiesmentioning
confidence: 99%